2012
DOI: 10.1063/1.3694798
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ammonia plasma and AlN passivation by plasma-enhanced atomic layer deposition

Abstract: Initial growth, refractive index, and crystallinity of thermal and plasma-enhanced atomic layer deposition AlN films J. Vac. Sci. Technol. A 33, 01A111 (2015); 10.1116/1.4898434Effects of interface oxidation on the transport behavior of the two-dimensional-electron-gas in AlGaN/GaN heterostructures by plasma-enhanced-atomic-layer-deposited AlN passivation J. Appl. Phys. 114, 144509 (2013) Surface passivation of GaAs by ammonia plasma and AlN fabricated by plasma-enhanced atomic layer deposition are compared. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Recently, using nitrogen passivation as a pre-gate treatment, good HfO 2 /In 0.53 Ga 0.47 As structure has been presented with low midgap D it and low equivalent oxide thickness (EOT) [4]. Other significant approaches of nitrogen passivation on III-V surfaces, aluminum nitride (AlN), have been proposed by thermal or plasma enhanced atomic layer deposition (PEALD) [5], [6]. Besides, post-gate treatment with fluorine (F) plasma has also been reported to optimize the high-k gate stack [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using nitrogen passivation as a pre-gate treatment, good HfO 2 /In 0.53 Ga 0.47 As structure has been presented with low midgap D it and low equivalent oxide thickness (EOT) [4]. Other significant approaches of nitrogen passivation on III-V surfaces, aluminum nitride (AlN), have been proposed by thermal or plasma enhanced atomic layer deposition (PEALD) [5], [6]. Besides, post-gate treatment with fluorine (F) plasma has also been reported to optimize the high-k gate stack [7].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] With the advantages of a self-limiting growth providing precise thickness control, atomic layer deposition (ALD) has recently been developed to deposit AlN at relatively low temperatures. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] The ALD of AlN can be performed by both thermal and plasma-enhanced modes (i.e., thermal ALD and PEALD, respectively). In thermal ALD, ammonia (NH 3 ) is commonly used as an N-source, in combination with various aluminum precursors, such as aluminum trichloride (AlCl 3 ), 13 trimethylaluminum [TMA, Al(CH 3 ) 3 ], [13][14][15] tris(dimethylamido)aluminum (Al 2 [N(CH 3 ) 2 ] 6 ), 16 and triethylaluminum [TEA, Al 2 (C 2 H 5 ) 6 ].…”
mentioning
confidence: 99%
“…In contrast, PEALD has been widely applied for depositing AlN films due to enhanced reactivity of the precursors in the presence of plasma, which can significantly reduce the growth temperature (i.e., down to 100-150 C). [18][19][20][21][22][23][24][25][26] The growth rates of ALD AlN are typically in the range of 0.4-1.5 A ˚/cycle. The studies on growth of ALD AlN have demonstrated an increase of the growth rate with increasing substrate temperature, although a narrow temperature window, in which the growth rate of PEALD AlN is temperature independent, has also been observed.…”
mentioning
confidence: 99%
“…However, the integration of III-V compound semiconductor and high dielectric constant materials is still limited by the inherently large amount of defect traps at the interfaces (1,2). Among many interfacial passivation efforts (3,4), PEALD-AlN has been proposed as a passivation method on both the p-GaAs substrates and the GaAs near-surface quantum well (NSQW) structures with unpinning Fermi level (5,6). In this work, we study the influence of PEALD-AlN passivation for both n-type and p-type In 0.53 Ga 0.47 As MOSCAPs by varying the PEALD plasma power.…”
Section: Introductionmentioning
confidence: 99%